Analysis of the Value and Role of Religious Education in the Structure of the Educational Curriculum to Strengthen Character Education and Social Cohesion - Ni Putu Sudewi Budhawati; I Wayan Agus Gunada (Jurnal Penelitian Agama Hindu, 2026)
The research aims to analyze the role of religious education in shaping the character of students oriented toward strengthening social cohesion. Plurality is a characteristic of Indonesian society, which carries the potential for social capital, but it also has the potential to trigger horizontal conflicts. The research focuses on how religious education plays a role in the formation of individual student character as a foundation for strengthening social harmony and cohesion. The research uses a qualitative approach grounded in hermeneutic phenomenology. The study’s findings show that religious education, integrated into the national curriculum, plays an important role in internalizing religious values in the educational process. This integration is not only a ritual aspect but also forms religious awareness, manifested in students’ daily religious attitudes and behaviors as agents of change in society. In the context of diversity, inclusive religious education will equip individual awareness with moral maturity, especially to appreciate differences. As a result, a strong religious character among students will lay the foundation for tolerance and the strengthening of social ties in Indonesian society. These findings may explain that religious education serves as a central instrument for strengthening national integration. This study is expected to serve as a theoretical reference for the development of future education and research policies, especially regarding socio-cultural dynamics in Indonesia, confirming that the maturity of an inclusive religious character is the key to maintaining the stability of the pluralistic Indonesian nation.